Presión arterial en caninos - monografía. - Avendaño Beltrán, María Alejandra (Universidad Antonio Nariño, 2021)
Blood pressure (BP) is a very useful physiological parameter for diagnosing diseases in human medicine. However, in veterinary medicine its determination is not yet part of daily practice (Graiff, 2005). Blood pressure can be measured directly by intra-arterial catheter or indirectly by devices that incorporate a compression cuff. (Brown et al., 2007). You need an artery of a certain caliber, peripheral, superficial and located in an area that can be pressed comfortably and evenly with a pneumatic cuff. If possible, it is preferable that the artery be at the level of the heart when making the measurement (Ynaraja, 2017). The results of the measurement of BP in animals are highly variable and depend on breed, temperament, patient position, measurement method and operator experience (Acierno et al, 2018). BP control mechanisms are inappropriately activated in AHT so that blood volume and blood pressure are maintained at higher levels (Joyner and Limberg, 2014). Thus causing damage to the cardiovascular, nervous, kidney and eye systems (Acierno et al, 2018).